Pengembangan Peralatan Simulasi Peralatan Aliran Daya Berbasis Fast Decoupled-Dependent Newton-Raphson dengan Program Interface-Based Delphi - Saini, Makmur; Tandioga, Remigius; Pangkung, Andareas; Yunus, A.M Shiddiq (INTEK: Jurnal Penelitian, 2017)
On one hand, the particular objective of this research is to yield the software program in order to control efficiently the important aspects in electric power systems which can be implemented in industries. In the other hand, the longterm objective is to extend the curriculum, syllabi, laboratory facilities, and to improve the abilities and qualities of graduates continuously either within State Polytechnic of Ujung Pandang or outside. Method used to achieve these objectives is making, design and implementation which will be last for two years. Simulator for generation system in the first stage of the research is balanced six-phase system yielded from the circuit of 3-one phase centre-tap transformers of 220/18 V, 15 A, as the supply of low-tension 3-phase system, which feeds six one-phase transformer of 18/220 V, 20 A, whose output as another balanced 3-phase system with 220 V/phase. From balanced 6-phase system, a balanced 3-phase will simulate generator number 1 and another balanced 3-phase will simulate that of number 2. Interface which is based on Delphi program is to switch all transmission lines. The result of experiment shows that voltages in the two generator busbars experience the significant drop voltage if they work separately, that are 20.5% - 36.4% and 20.5% - 63.6% for generator number 1 and number 2 respectively, for one to three load busbars operated sequentially, which also reveals that greatest voltage drop occurs in the generator busbar with most lines supplied. Simulating the two generators working simultaneously, then voltage drops are more significant, that are 65.9% - 72.7% and 65.9% - 79.5% for generator number 1 and number 2 respectively, for one to three load busbars operated sequentially, which also proves that transformer bank as generator simulator needs to increase its current capacity.